PERBEDAAN RESILIENSI ANTARA REMAJA YANG HIDUP DALAM KELUARGA LENGKAP, KELUARGA SINGLE PARENT, DAN REMAJA YANG HIDUP DI PANTI ASUHAN - Purwanti, Wahyu; Aulia, Lailatuzzahro Al-Akhda (ILMU PSIKOLOGI, 2017)
The development of teen personality does not always match what is expected. The events that they have experienced can affect their attitudes and personalities. It can be caused by many factors, one of which is the environmental factor, especially the family. In order to deal with any unpleasant event, adolescents need a capability that called resilience. The purpose of this study was to determine whether or not difference in resilience between adolescents who living in complete families, single parent families, and adolescents who living in orphanages. The population in this study were adolescents in Pandaan and Gading Rejo. This research used quota sampling technique. The result of analysis data that used Anava-1 path is FOA=2,23 with ttab 5%=3.00 indicates that there is no difference of mean resilience adolescents who living in complete family, single parent family, and adolescents who living in orphanages. The hypothesis that there is a difference in resilience between adolescents living in complete families, single parent families, and adolescents who living in orphanages, is rejected.